SYNTHESIS OF ACETIC ACID FROM ETHANOL BY ELECTROOXIDATION TECHNIQUE USING Ni-Cu-PVC ELECTRODE - Riyanto Riyanto; Mohamed Rozali Othman; Jumat Salimon (Universitas Gadjah Mada, 2008)
A usage of Ni-Cu-PVC electrode for the oxidation of ethanol by electrochemical technique will be reported in this paper. In this work, the effect of electrodes on the yields of acetic acid was determined. Electrode used was made of the mixtures of Ni powder, Cu powder and of polyvinyl chloride (PVC) with various percentages. Electrooxidation of 0.20 M ethanol in 0.16 M KOH (24 mL) were carried out using chrono coulometry (CC) at a potential of 1050 mV for 6 hours with continious stirring. Electrooxdation result obtained was analyzed using High Performance Liquid Chromatography (HPLC). The test result shows that the composition of Ni:Cu:PVC at 75:20:5 have higher efficiency in the electrooxidation of ethanol to acetic acid.